Dynamic Transcriptome-Based Weighted Gene Co-expression Network Analysis Reveals Key Modules and Hub Genes Associated With the Structure and Nutrient Formation of Endosperm for Wax Corn - Li, Tingchun; Kong, Fanna; Dong, Qing; Xu, Dafeng; Liu, Guihu; Lei, Yanli; Yang, Huaying; Zhou, Yingbing; Li, Cheng (Frontiers in Plant Science, 2022)
The endosperm of corn kernel consists of two components, a horny endosperm, and a floury endosperm. In the experiment, a kind of floury endosperm corn was identified. The result of phenotypic trait analysis and determination of amino acid content showed that the floury endosperm filled with the small, loose, and scattered irregular spherical shape starch granules and contained higher content of amino acid. The starch biochemical properties are similar between floury corns and regular flint corn. By using dynamically comparative transcriptome analysis of endosperm at 20, 25, and 30 DAP, a total of 113.42 million raw reads and 50.508 thousand genes were obtained. By using the weighted gene co-expression network analysis, 806 genes and six modules were identified. And the turquoise module with 459 genes was proved to be the key module closely related to the floury endosperm formation. Nine zein genes in turquoise module, including two zein-alpha A20 (Zm00001d019155 and Zm00001d019156), two zein-alpha A30 (Zm00001d048849 and Zm00001d048850), one 50 kDa gamma-zein (Zm00001d020591), one 22 kDa alpha-zein 14 (Zm00001d048817), one zein-alpha 19D1 (Zm00001d030855), one zein-alpha 19B1 (Zm00001d048848), and one FLOURY 2 (Zm00001d048808) were identified closely related the floury endosperm formation. Both zein-alpha 19B1 (Zm00001d048848) and zein-alpha A30 (Zm00001d048850) function as source genes with the highest expression level in floury endosperm and the maximum Log2FC values (W056 vs W042). These results may provide the supplementary molecular mechanism of structure and nutrient formation for the floury endosperm of maize. Key words: Waxy corn; Floury endosperm; Dynamic comparative transcriptome analys